Doping mechanism of Zn2+ ions in Zn-doped TiO2 prepared by a sol–gel method1. Issue 27 (21st July 2015) - Yu, Yanlong; Wang, Jingsheng; Li, Wei; Zheng, Wenjun; Cao, Yaan
<x xml:space="preserve">Abstract</x> The introduced Zn2+ ions first exist as O–Zn–Cl species on the surface of TiO2. With the increase in calcination temperature, the O–Zn–Cl species would transform into ZnTiO3, which would induce the formation of rutile, resulting in a decrease in the temperature for phase transition.